2021
DOI: 10.1037/pspp0000281
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning supports utilitarian resolutions to moral dilemmas across diverse measures.

Abstract: Sacrificial moral dilemmas elicit a strong conflict between the motive to not personally harm someone and the competing motive to achieving the greater good, which is often described as the "utilitarian" response. Some prior research suggests that reasoning abilities and deliberative cognitive style are associated with endorsement of utilitarian solutions, but as has more recently been emphasized, both conceptual and methodological issues leave open the possibility that utilitarian responses are due instead to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
61
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 155 publications
7
61
1
1
Order By: Relevance
“…Apart from demonstrating that the PD procedure can detect patterns of deontological and utilitarian inclinations that remained invisible in earlier moral dilemma research, which relied on a one-dimensional measure of moral inclinations (the percentage of utilitarian responses), the PD studies have provided evidence that the U parameter indeed measures, at least primarily, the person's tendency to maximize the overall benefit (e.g., Conway and Gawronski, 2013;Conway et al, 2018a; see also Patil et al, 2020). By contrast, the interpretation of the D parameter is somewhat less clear.…”
Section: The Process Dissociation Approach To Moral Judgmentmentioning
confidence: 99%
“…Apart from demonstrating that the PD procedure can detect patterns of deontological and utilitarian inclinations that remained invisible in earlier moral dilemma research, which relied on a one-dimensional measure of moral inclinations (the percentage of utilitarian responses), the PD studies have provided evidence that the U parameter indeed measures, at least primarily, the person's tendency to maximize the overall benefit (e.g., Conway and Gawronski, 2013;Conway et al, 2018a; see also Patil et al, 2020). By contrast, the interpretation of the D parameter is somewhat less clear.…”
Section: The Process Dissociation Approach To Moral Judgmentmentioning
confidence: 99%
“…We must note that there have been consistent results showing connections between specific moral PDP parameters and external variables such as gender (Friesdorf et al, 2015) or reasoning style (Byrd & Conway, 2019;Conway & Gawronski, 2013;Patil et al, 2020).…”
Section: Discussionmentioning
confidence: 74%
“…The effect of cognitive load as well as sex differences found using the traditional sacrificial dilemmas (Fumagalli et al, 2010;Greene et al, 2008), have been verified using the PDP or similar models (Conway at al., 2017;Friesdorf et al, 2015). Using the PDP, experimenters have found that utilitarian but not deontological inclinations are related to other cognitive measures such as the cognitive reflection test (Patil et al, 2020). Thus, the PDP seems to replicate results produced by more traditional measurements, but it allows for more specific inferences about where, specifically, individual differences manifest, and what kinds of processes are affected by experimental manipulations.…”
Section: Measuring Utilitarian and Deontological Dispositionsmentioning
confidence: 98%
“…Although a logical reflection measure has correlated with harm-aversion tendencies before, arithmetic reflection (assessed by the CRT) has not (Byrd and Conway, 2019). The fact that more arithmetically correct answers on the CRT predicted the rejection of harmful action when harm resulted in a "greater good" and when it did not challenges the view that a more arithmetic focus is responsible for moral judgments that prioritize the number of lives saved (Byrd and Conway, 2019;Patil et al, 2020). An association between CRT performance and harm aversion is also counterintuitive to dual-process perspectives (Greene et al, 2001) that propose the rejection of harmful actions is associated with a faster, more emotional decision-making pathway that we might expect to negatively correlate with intuitive responses on the CRT (e.g., Kahneman and Frederick, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In support of a dual-process conceptualization, emotional arousal predicts deontological preferences (Szekely and Miu, 2015), and performing or witnessing harmful actions correlates with measures of cardiac arousal (Cushman et al, 2012;Parton and McGinley, 2019). More calculative reasoning styles have been associated with utilitarian response tendencies (Patil et al, 2020), and successful performance on the Cognitive Reflection Task (CRT; Frederick, 2005) is associated with increased utilitarian judgments, potentially due to its association with cognitive deliberation (Baron et al, 2015). The CRT task includes questions that have both correct and "intuitive" answers and can be scored according to correct versus intuitive responses (Erceg and Bubić, 2017).…”
Section: Introductionmentioning
confidence: 95%